Hubungan Tingkat Pengetahuan Ibu Tentang Perawatan Gigi Dengan Karies Gigi Anak Usia Pra Sekolah 4-5 Tahun - Arsad Arsad; Yulistina Yulistina; Sulastri S; Sultan Amin Yasin; Utari Zulkaidah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Pre-school age children are a period of child growth. Caries is a case experienced by pre-school age children. The 2018 Basic Health Research, the prevalence of dental caries in children aged 3-4 years in Indonesia is 36.4%, the prevalence of dental caries in pre-school children in South Sulawesi is 73.6%, the prevalence of dental caries in East Luwu is 82.8%, and the prevalence of dental caries at the age of pre-children as in Nuha District 89.2%. This condition is very concerning considering that pre-school children still need the role of parents in caring for their health, especially dental health. In this case, parental knowledge is needed in guiding and giving more attention so that children do not experience caries. This study aims to determine the relationship between the level of knowledge of mothers about dental care and dental caries in pre-school aged children 4-5 years at Al-Ikhwan Kindergarten. The research method used is analytic observational with a retrospective approach. This research was conducted in May 2023 with the subjects of this study being parents, especially mothers whose children attended TK Al-Ikhwan as many as 89 people. Collecting data using a questionnaire sheet. Analysis of research data using Univariate and Bivariate Test analysis. The level of parents' knowledge about dental health is mostly in the sufficient category (47, 21%). The majority of respondents experienced media caries (61.79%). Ha is accepted with ƿ Value – 0.006, correlation coefficient -0.946. There is a relationship between the level of parental knowledge about dental health and the occurrence of caries in preschool children aged 4-5 years at TK-Al Ikhwan, East Luwu Regency.